Pengentasan Stunting Dengan Pemberian PMT Dan Penyebaran Brosur Pentingnya Posyandu Oleh Mahasiswa KUKERTA UNRI 2023 Desa Teluk Latak - Taryono Taryono; Muhammad Rifa’i; Roza Auliya Rosana MZ; Nandita Oktaviana; Sri Rahayu; Rifka Safira; Awibbi Permana Meidil Putra; Ajeng Retno Setiawati; Nolianus Hogejau; Yessy Maharani; Yuni Rahmawati Simangunsong (FKIP, Universitas Palangka Raya, 2023)
One strategy that can be carried out by KUKERTA UNRI 2023 students to improve public health in Teluk Latak Village is to hold community service activities in Teluk Latak Village. One of the health problems that commonly occurs in villages is stunting. Stunting is a description of chronic malnutrition during the growth and development of children starting from the beginning of their lives. Stunting can be caused by many factors, some of which are the characteristics of the toddler itself and socio-economic conditions. The KUKERTA UNRI 2023 Student Team contributed to monthly posyandu activities as an effort to prevent stunting which were held at three posyandu in Teluk Latak Village. This activity includes measuring the child's height, weight, measuring several other parts of the child's body and exploring the child's level of development. The activity of providing PMT (Providing Additional Food) and distributing brochures on the importance of posyandu to the people of Teluk Latak Village was also carried out to increase community literacy about the importance of posyandu every month. This article emphasizes the importance of a participatory and collaborative approach in preventing stunting in Teluk Latak Village, as well as how KUKERTA UNRI 2023 students can make changes that will ultimately improve the welfare of children in Teluk Latak Village. It is hoped that the participation of KUKERTA UNRI 2023 students can create a positive synergy between higher education institutions, the community and the village government in improving the quality of life for children in Teluk Latak Village.